Design of Hydraulic Bulging Die for Automobile Torsion Beam and Optimization of Forming Process Parameters - Kefan Yang; Youmin Wang; Kexun Fu (Advances in Materials Science and Engineering)
The hydraulic bulging technology of tubes can provide hollow parts with special-shaped cross sections. Its manufacturing process can effectively improve material utilization and product accuracy and reduce the number and cost of molds. However, the hydraulic bulging process of parts is very complicated. The size of the tube blank, the design of the loading route, and the forming process parameters will have an effect on the molding quality. Closed tubular torsion automobile beam is considered as the research object to study hydraulic bulging die design and optimize forming process parameters. CATIA software is used to design torsion beam product structure and hydraulic bulging die. AMESim software is employed to design hydraulic synchronous control system for cylinders on both sides of the hydraulic bulging die. Mathematical control model is established and verified in Simulink software. DYNAFORM software is applied to conduct numerical simulation of hydraulic expansion. The supporting pressure, molding pressure, friction coefficient, and feeding quantity are taken as orthogonal experiment level factors. Maximum thinning and maximum thickening rates are taken as hydraulic pressure expansion evaluation indexes to complete the orthogonal experiments. Main molding process parameters are analyzed via orthogonal experiment results and optimized by employing the Taguchi method. Optimal hydraulic bulging parameters are obtained as follows: supporting pressure of 20 MPa, molding pressure of 150 MPa, feeding quantity of 25 mm, and friction coefficient of 0.075. Simulation analysis results indicate that the maximum thinning rate is equal to 9.013%, while the maximum thickening rate is equal to 16.523%. Finally, the design of hydraulic bulging die for torsion beam was completed, and its forming process parameters were optimized.